A Brief History of the Evolution of the Hungarian Police Anti-Terror Units (1987–2010) - Kiss, Dávid (Magyar Rendészet, 2023)
This paper will attempt to cover the history and evolution of the Hungarian anti-terror capability and the evolution of the dedicated Hungarian police anti-terror units from 1987 up to 2010 from a historical perspective. By using interviews and memoires of former unit members, contemporary manuals and media sources, and presenting the legal background, this paper will attempt to highlight the historical significance, the cultural heritage, and the tactical methodology behind the evolution of the Hungarian stance on terrorism and anti-terrorism from its most acute aspect, the boots on the ground and the operators behind the orders. This paper also includes a brief history and description on the different uniforms, equipment and weapon systems, highlighting the changes in tactical approaches, and varying opportunities in obtaining or developing more modern and advanced technology.